Evaluating the impact of agro-entrepreneurial activities in an academic health promotion program at a children’s activity centre in Kuala Muda / Siti Nur Fadzilah Muhsain ... [et al.] - Muhsain, Siti Nur Fadzilah; Wan Ismail, Wan Nordini Hasnor; Ibrahim, Nurul Alyaa; Muhsain, Siti Nur Fathini; Yusmaniar, Yusmaniar (Universiti Teknologi MARA, Perlis, 2025)
In 2016, the government launched the Young Agropreneur Program to encourage young people to participate in agriculture, agri-food, and entrepreneurship. To support the growth of young agropreneurs, promoting interest from an early age is essential. Indeed, some programs target schoolchildren to cultivate this interest, but their effectiveness remains uncertain. This study examines children's interest in agropreneurship at the Pusat Aktiviti Kanak-Kanak (PAKK) Kuala Muda, Penaga. The objective is to assess the level of attitude and knowledge among children exposed to activities by Universiti Teknologi MARA Cawangan Pulau Pinang (UiTMCPP) that enhance knowledge, skills, and interest in entrepreneurship, agriculture, and health. The study sample involves 20 children, with data collected through interviews and observations during activities. Results indicate that children’s knowledge, awareness, and interest can influence their interests towards agropreneurship. However, there is potential to improve their attitudes and awareness. This study provides preliminary insights for policymakers to encourage interest in agropreneurship from an early age through targeted support schemes, helping higher education institutions design focused programs that foster greater engagement in this field.